Double Dividend : Power and Agriculture Nexus in Sub-Saharan Africa - Banerjee, Sudeshna Ghosh; Malik, Kabir; Tipping, Andrew; Besnard, Juliette; Nash, John (World Bank, Washington, DC, 2017)
Increasing access to modern electricity services in Sub-Saharan Africa is one of the main development challenges facing the world over the next two decades. The rural economies are overwhelmingly dependent on agriculture; in fact, agriculture and agribusiness comprise nearly half of Africa’s gross domestic product (GDP). These enterprises require electricity to grow to their potential, while the expansion of rural energy services needs consumers with consistent power needs to serve as a reliable revenue source. Can agriculture and energy come together in Sub-Saharan Africa to offer a double dividend with benefits to enterprises, households, utilities, and private-sector service providers? This is the central question of this study. Combining agricultural load with other household and commercial power demand can increase the feasibility of extending the grid or creating opportunities for independent power producers and mini-grid operators. Drawing on a suite of case studies, this study offers insights on what it will take to operationalize the opportunities and address the challenges for power-agriculture integration in Africa.